Adaptive clinical trials: overview 2 - Shyr, Yu (Henry Stewart Talks, 2017)
Adaptive randomization clinical trials: based on baseline covariates, Adaptive minimization randomization, Adaptive randomization clinical trials: based on study outcome, Biased Urn, Response-adaptive randomization: ECMO, Example (ECMO), randomization scheme, Biomarker-adaptive clinical trials design, Prognostic marker, Predictive marker, Umbrella & basket trials